A Daily Diary Study on Sleep Quality and Procrastination at Work: The Moderating Role of Trait Self-Control - van Eerde, Wendelien; Venus, Merlijn (Frontiers in Psychology, 2018)
Background: This daily diary study investigates the relation between sleep quality during the night and its effect on procrastination at work during the next workday. Previous research has shown that sleep quality is an important variable for work behavior at the daily level, including employee performance, safety, health, and attitudes, such as work engagement. Also, sleep quality has been found to be negatively related to next-day work procrastination. However, these studies did not address trait differences that may be involved. In other words, they have not investigated whether all employees experience the effects of sleep quality on procrastination similarly. We explore the moderating effect of trait self-control. Method: 71 employees working in various industries completed a one-shot general electronic questionnaire (to assess trait self-control). Subsequently, these employees received two daily electronic questionnaires to assess sleep quality and procrastination over the course of ten work days, resulting in 465 pairs of matched morning-afternoon measurements (61% response). Results: Results of multilevel regression analyses showed that sleep quality was negatively related to work procrastination the next day. Sleep quality, however, also interacted with trait self-control in impacting work procrastination, such that low sleep quality affected employees low in trait self-control, but not employees high in trait self-control. Conclusions: The findings of this study qualify earlier research showing the relation between procrastination and sleep quality. We show that the relation is only present for those who have low trait self-control; employees with high trait self-control tend to be immune to low sleep quality. Thus, general advice or interventions to improve sleep quality may be restricted to a selection of employees that are truly affected.